Brain spatial reconciliation through multisensory integration in the impact of pandemic fatigue on workplace - Arinta, Rizka Tri; Satwiko, Prasasto; Widjaja, Robert Rianto; Kusrohmaniah, Sri (Frontiers in Human Neuroscience, 2024)
The COVID-19 pandemic has highlighted the prevalence of fatigue, reduced interpersonal interaction, and heightened stress in work environments. The intersection of neuroscience and architecture underscores how intricate spatial perceptions are shaped by multisensory stimuli, profoundly influencing workers’ wellbeing. In this study, EEG and VR technologies, specifically the Emotiv Epoc X, were employed to gather data on perception and cognition. Through the analysis of statistical data, independent component analysis (ICA), and perception metrics, the research explored the brain’s responses to various sensory stimuli encountered in the workplace. This research aims to examine how individuals adapt to work environments that expose them to multiple sensory stimuli, by observing brain activity and perception processing. The findings indicate that integrating multisensory stimuli, such as light, sound, and smell, can significantly enhance employees’ performance and perception of their workspaces. The Bayesian brain mechanism, which prioritizes key sensorimotor inputs, plays a critical role in continuously adjusting the brain’s perception of sensory information. This mechanism operates through sensory weighting, wherein the brain assigns greater importance to the most relevant sensory inputs, depending on the specific demands of the work environment. For instance, visual elements, such as lighting and color schemes, along with olfactory stimuli in high-density environments, are instrumental in shaping workers’ perceptions of the spatial dimensions, ambiance, and emotional responses within the workplace. This underscores the potential of multisensory integration as a form of reconciliation between architecture and the cognitive demands of office spaces.